2020
DOI: 10.3390/pathogens9080664
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens Manipulating Tick Behavior—Through a Glass, Darkly

Abstract: Pathogens can manipulate the phenotypic traits of their hosts and vectors, maximizing their own fitness. Among the phenotypic traits that can be modified, manipulating vector behavior represents one of the most fascinating facets. How pathogens infection affects behavioral traits of key insect vectors has been extensively investigated. Major examples include Plasmodium, Leishmania and Trypanosoma spp. manipulating the behavior of mosquitoes, sand flies and kissing bugs, respectively. However, research on how p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 91 publications
(119 reference statements)
1
65
0
Order By: Relevance
“…In the current study, we confirmed the expression of a complete Ixodes neuropeptidome in ISE6 cells. Considering that neuropeptides are regulators of all tick physiological processes and pathogens modulate tick physiology [ 32 ], our study suggests that ISE6 cells are an effective in vitro archetype for investigating TBP interactions with vital elements (i.e., neuropeptides) of the tick synganglion. Therefore, investigating tick–pathogen interactions by enlisting parallel, yet similar, cell-types (i.e., ISE6 cells and tick synganglion) may contribute to advancing tick control strategies to prevent TBP transmission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, we confirmed the expression of a complete Ixodes neuropeptidome in ISE6 cells. Considering that neuropeptides are regulators of all tick physiological processes and pathogens modulate tick physiology [ 32 ], our study suggests that ISE6 cells are an effective in vitro archetype for investigating TBP interactions with vital elements (i.e., neuropeptides) of the tick synganglion. Therefore, investigating tick–pathogen interactions by enlisting parallel, yet similar, cell-types (i.e., ISE6 cells and tick synganglion) may contribute to advancing tick control strategies to prevent TBP transmission.…”
Section: Discussionmentioning
confidence: 99%
“…A. phagocytophilum induces tissue-specific transcriptional reprogramming, thereby affecting different cellular functions in infected tick [ 21 , 22 , 23 , 26 , 27 , 28 ]. A. phagocytophilum infection also alters tick physiology and behavior [ 32 ]. For example, A. phagocytophilum -infected ticks were more fitted to survive in cold temperatures [ 34 ] or desiccating conditions [ 35 ] compared to uninfected ticks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, vector-borne pathogens can manipulate their arthropod vectors (e.g., increase the biting rate, shift resources from reproduction to survival) to increase their own transmission, and thereby increase the R 0 of the vector-borne disease [8][9][10][11] . Measuring the effects of vector-borne pathogens on the tness of their arthropod vectors is therefore important for understanding the epidemiology of vector-borne diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Hard ticks of the genus Ixodes transmit a diversity of tick-borne pathogens such as the spirochete bacteria belonging to the Borrelia burgdorferi sensu lato (sl) complex, which includes the causative agents of Lyme disease 3,26,27 . Some reviews have suggested that B. burgdorferi sl can adaptively manipulate its Ixodes tick vector to enhance its own transmission, and hence the R 0 of Lyme disease 11,28 . Ixodes ticks infected with B. burgdorferi sl differ from their uninfected counterparts in a number of tick phenotypes including questing behaviour, survival rates, body weight, and energy reserves [29][30][31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%